Body measurements and testosteron level of male Timor deer (Rusa timorensis) at various hierarchies - Samsudewa, D.; Capitan, S. S.; Sevilla, C. C,; Vega, R. S. A.; Ocampo, P. P. (Diponegoro University, 2017)
The aim of this research was to observe body (neck, chest and scrotum) circumferences and testosterone level of α-male, β-male and subordinate male Timor deer reared under captivity after establisment of the dominance hierarchy. Twelve males (51 ± 6 months old; 68.29 ± 8.41 kg body weight and in same antler stages) were used in this research. The bucks was grouped into three stall each containing four bucks. ELISA kit and tape measurements were used for plasma Testosterone assay and body measurement, respectively. Data was collected before and 43 days after establishment of the dominance hierarchy. Wilcoxon signed ranks test and Kruskal-Wallis H test of non-parametric analysis was used. Significant difference was tested with Mann-Whitney U test. The results showed no significantly different for body circumferences (neck, chest, scrotum) and testosterone level of male Timor deer before establishment of dominance hierarchy. Chest and scrotum circumferences of male Timor deer after establihment of dominance hierarchy showed no significantly different. Significantly difference shown on parameter neck circumference (P<0.05; χ2 = 8.74) and testosteron level (P<0.05; χ2 = 7.87) after establishment of dominance hierarchy. In conclusion, dominance hierarchy affected the testosterone level and body measurement.